Jurisprudential Investigation of Wife’s Inheritance from Land by Emphasizing Famous Arguments of Later Scholars and Seyed Murteza - Sayyed Alireza amin; Ashkan Naeimi (مطالعات فقه و حقوق اسلامی)
Concerning the subject of the wife’s inheritance from land, which is an adjunct issue in the field of women inheritance, various perspectives have been raised in jurisprudential books. Different perspectives, which have originated from different scholars’ interpretations, have also found their way into the legislative domains, as with the amendments in the February of 2008 in articles 946 and 948 of the Civil Code, the theory of the wife’s share of the price of the immovable property (the view by Seyed Murteza) replaced the theory of the wife’s deprivation of the price of the immovable property and its kind (the view by later scholars). Doubts about the influence of the egalitarian movements calling for the equality of rights between men and women in some jurisprudential inferences, and also the outstanding role of legislature in safeguarding Islamic teachings require a fair investigation into the wife’s inheritance from land so that the true theory in this regard is clarified. This study used the descriptive-analytical method to demonstrate the outstanding theory of later scholars, upon which the wife, with or without children, does not inherit from her deceased husband’s price of land and its kind, either residential or agricultural, though she inherits from the price of buildings.